TEACHERS’ PERCEPTION ON THE EVECTIVENESS USING GRAMMARLY AS A TOOL FOR WRITING ASSESSMENT - Siti Deti Wijayanti; Sumarta Sumarta; Maya Rahmawati (Linguistik : Jurnal Bahasa dan Sastra, 2021)
In this digital era the progress writing assessment changes rapidly to monitor and determine students writing has developed tools in order to assessing the students’ writing automatically to help the teacher. The tools called Automated Writing Evaluation (AWE) which are more commonly known as computer-generated feedback. In other hand, Grammarly as one of developed AWE program is effective to help teachers in correcting EFL writing. Most previous study, however, are primarily concerned with students’ improvement and perceptions using Grammarly. While, limited study taking yet on Teachers’ perception on the effectiveness of Grammarly application as a tool of writing assessment. This research aimed at investigating teachers’ perception on the effectiveness of Grammarly application as a tool of writing assessment. This research used the qualitative approach with descriptive case study design. The subject of the research was three EFL teacher who has been teaching English language for many years and used grammarly as a tool for writing assessment.  The findings from three participants indicates that the teachers respond positive perception. Positive perception refers toward that grammarly had helped the teachers in assessing students’ writing assessment effectively and efficiently at gramamar, punctuation and spelling features based on principle assessment by (brown, 2004) that is practically, reliability, validity, authenticity and washback.